1982
DOI: 10.2307/134918
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Equalization Payments in a Federal System of Government: A Synthesis and Extension of Recent Results

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
215
0
9

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(228 citation statements)
references
References 22 publications
4
215
0
9
Order By: Relevance
“…He emphasizes that the redistributive power of sub-national governments will lead to political programs that do not conform to the national interest. Moreover, sub-national redistributive power will result in fiscal competition with a sub-optimal outcome from a national equity point of view [see also Boadway and Flatters (1982)]. Another argument is related to the budgetary power of central and local governments.…”
Section: The Theoretical Link Between Decentralization and Regional Dmentioning
confidence: 99%
“…He emphasizes that the redistributive power of sub-national governments will lead to political programs that do not conform to the national interest. Moreover, sub-national redistributive power will result in fiscal competition with a sub-optimal outcome from a national equity point of view [see also Boadway and Flatters (1982)]. Another argument is related to the budgetary power of central and local governments.…”
Section: The Theoretical Link Between Decentralization and Regional Dmentioning
confidence: 99%
“…However, we should mention that stability of the migration equilibrium requires the denominator N to be negative, ^ -N < 0. Instability arises in the case of an underpopulated federal economy [see Stiglitz (1977) and Boadway and Flatters (1982)]. If a socially efficient population distribution is achieved, stability requires that the equalized marginal net benefit of mobile households to both regions (from the viewpoint of the single region), f l n -^ n J u 'J nn + ^ + n,n 'J" n , must be negative.…”
Section: Social Optimummentioning
confidence: 99%
“…Typically, previous models on this subject ignore any mobility of households across regions. 1 Another approach in the literature analyzes the supply of regional (or local) public goods without spillovers in the presence of highly mo bile households [see, e.g., Hartwick (1980), Boadway (1982), Boadway and Flatters (1982), Wildasin (1980) and(1986), and Myers (1990)]. Recently, Myers (1990) has demonstrated that in a Nash-equilibrium of competing regional governments not only is an optimal supply of regional public goods (without spillovers) achieved, but also an optimal distribution of mobile households across regions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the allocation of labour across regions will generally not be efficient. Transfers between regions, if determined before regional decisions are made, can be set to induce the efficient allocation of population (Boadway and Flatters, 1982). On the other hand, if transfers are determined after regional policies, regional governments will tend to over-provide regional public goods in order to elicit larger transfers from the federal government.…”
Section: Perfect Mobility With Regional Public Goodsmentioning
confidence: 99%